Studi empiris determinasi harga saham pada perusahaan pertambangan di Indonesia - Asmarawati, Budi; Purwantorojati, Budhi; Wiratno, Dwi Haryono; Niandari, Nanik (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This researh aims to determine the effect of return on equity, debt equity ratio, earnings per share, book value per share, and stock beta on stock prices in mining companies listed on the Indonesia Stock Exchange for the 2016-2020 period. This type of research is causal explanatory research. The population in this study were 49 mining companies listed on the IDX. The sample in this study used a purposive sampling method of 21 companies. Source of data in the form of secondary data. The data was obtained from www.idx.co.id and www.finance.yahoo.com. Methods of data collection by using the technique of observation documentation. This study uses quantitative analysis methods including classical assumption test, multiple linear regression, statistical test (t), simultaneous test(F), and coefficient of determination (R2). The results showed that 1). Partially, the return on equity variable has a positive and significant effect on stock prices, while partially the debt equity ratio, earnings per share, book value per share, and stock beta variables have no significant effect on stock prices. 2). Simultaneously return on equity, debt equity ratio, earning per share, book value per share, and stock beta have a significant effect on stock prices with a contribution of 25.60% while the remaining 74.40% is influenced by other factors.